ANALYSIS OF SOCIAL AND GOVERNANCE ASPECTS IN MSME FINANCING AND THE DEVELOPMENT OF SUFIC MODELS TO SUPPORT SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Nina Nurkomalasari (El-Ecosy : Jurnal Ekonomi dan Keuangan Islam, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important and highly strategic role in achieving the Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty) and SDG 8 (Decent Work and Economic Growth). MSMEs contribute more than 60% to the national Gross Domestic Product (GDP), provide 97% of employment, and number more than 64 million units, demonstrating that the sustainability of MSMEs affects national social and economic stability. Although according to data, MSME financing continues to increase and financial literacy, especially among business actors, shows a positive increase, the risk of non-performing loans (NPLs) in MSMEs has increased. This situation shows that there is an imbalance between increased financing for MSMEs, social aspects, and governance aspects. The research method used is a qualitative descriptive method supported by secondary data. The results of the study show that MSME financing has fulfilled the Social dimension of Environmental, Social, and Governance (ESG) through increased access to capital and job creation, but it is not yet fully supported by adequate Governance practices at the business level. The Sustainable Financial Clinic (SUFIC) model was developed as a combination of systematic financial literacy training and a sustainable coaching clinic-based mentoring approach, which aims to improve the quality of financial management, reduce the risk of default in financing, and strengthen business sustainability. The implementation of SUFIC is expected to become a model for strengthening sustainable MSME financing governance and contribute to the achievement of SDGs 1 and SDGs 8 in a more optimal manner.